Designed p-type graphene quantum dots to heal interface charge transfer in Sn-Pb perovskite solar cells. (July 2022) - Guo, Tonghui; Wang, Huayang; Han, Wenhua; Zhang, Jing; Wang, Changlei; Ma, Tianshu; Zhang, Zequn; Deng, Zhiqiang; Chen, Da; Xu, Wenwu; Liu, Xiaohui; Huang, Like; et al.
Abstract: In Sn-Pb based low bandgap perovskite solar cells (LB-PSCs), the large energy loss of ~0.5 eV lags its development, originating from unfavorable band alignment at the interface and serious charge recombination in the device. Here, judiciously designed graphene quantum dots by functional N/Cl doping are applied at PEDOT:PSS/perovskite interface to modulate the energy level and charge transfer simultaneously. Among three designed graphene quantum dots, the N, Cl codoped one (N, Cl-GQDs) induces the best band alignment, because of the enhanced p-doping. Besides, N, Cl-GQDs best regulate the charge distribution and passivate the defect states at the interface by π-conjugated effect and electronegative Cl, paving the way for efficient interface charge transport. Upon N, Cl-GQDs optimization, the FA0.6 MA0.4 Sn0.6 Pb0.4 I3 based PSCs achieves impressive efficiency of 21.5% (1 sun, AM1.5) with a high photovoltage of ~0.89 V (energy loss of ~0.36 eV) and fill factor over 80%, which are among the best parameters in reported LB-PSCs. The N, Cl-GQDs modified device exhibits the best shelf stability after 1000 h, due to the least trap states and reformative interface. This work highlights designed graphene quantum dots for photovoltaic applications. Graphical Abstract: Upon N, Cl-GQDs optimization, the FA0.6 MA0.4 Sn0.6 Pb0.4 I3 based PSCs achieves impressive efficiency of 21.5% (1 sun, AM1.5) with a high photovoltage of ~0.89 V (energy loss of ~0.36 eV) and fill factor over 80%. ga1 Highlights: Designed GQDs are applied at PEDOT:PSS/PVK interface to modulate the energy level and charge transfer simultaneously. N, Cl-GQDs regulate the interface charge distribution and passivate the defects, guaranteeing efficient charge transport. Sn-Pb based PSCs achieve impressive efficiency of 21.5%, which are among the best parameters in reported low bandgap-PSCs.